The effect of Posner model on the acquisition of historical concepts among students of the second intermediate grade - sagban, mohammed khader (Al-Adab Journal, 2021)
The research aims to identify the effect of the Posner model on acquiring historical concepts among middle school students, and to achieve the research goal, the researcher set the following: hypothesis There is no statistically significant difference at the level (0.05) between the average scores of students of the experimental group who studied the history subject in the Posner model and the mean of the scores of the controlling group who studied the same subject according to the usual method, this research is determined by a sample of the average second grade students in middle school day In Baghdad / Al-Rusafa third governorate, and the concepts found in the first three chapters of Arab Islamic history, the researcher followed intentionally (Tunis School for Boys) which includes four people for the second intermediate grade, and randomly chose Division A to represent the experimental group with (33) students while Division (B) represented the control group at (34) students, and the researcher rewarded statistically between the students of the two research groups by using the T-test for two independent samples in the following variables: (Previous knowledge test, chronological age calculated by months, IQ test scores, and history subject scores for the previous year) After the researcher identified the subjects of the scientific subject to be studied during the experiment represented in the first three chapters of the book on Arab Islamic history, the researcher formulated behavioral goals, promising plans Her teaching, and it was presented to a group of specialized experts to judge its validity, then the necessary adjustments were made and ready to be applied in the light of their opinions. For the purpose of measuring the extent to which students of the two research groups acquired the concepts that he studied, the researcher prepared a test consisting of (51) multiple-choice test items. The researcher confirmed the validity of the test and the calculation of its reliability, and of the discriminatory forces, coefficients of difficulty of the (objective) paragraph and the effectiveness of the wrong alternatives, and the experiment lasted 9 weeks. T-test for two independent samples (T-test) to find out the significance of the difference at the level (05.05) between the two research groups. It became clear what follows the presence of a statistically significant difference at the level of significance (05.0) between the average scores of students of the experimental group who studied the history subject according to a model Posner and the degrees of the control group who studied the same subject according to the usual method of testing the acquisition of historical concepts and the result was in favor of the experimental group.